Subsidy policy and its effect on social housing acquisition in San Luis Potosi, Mexico - López-Mares, Lourdes Marcela; Parra-Rodríguez, Omar (Revista de Urbanismo, 2024)
Since the 1970s, the social housing sector in Latin America underwent market-led transformations that reduced State intervention and boosted participation by private developers and financial institutions. Their participation increased the housing supply but left behind the poorest sectors of the population for whom this type of housing remains unaffordable. Subsidy policies seek to promote affordability, either by directly providing workers with down payment funds or by injecting money into the production chain to reduce housing prices. Their implementation, however, remains marginal and shows a downward trend while housing costs steadily continue to rise. Even if subsidies are central to remedying the affordability gap left by market-led social housing policies in Latin America, few studies include them as a variable that would help understand the social housing production cycle and project potential scenarios. This study applies a dynamic model to simulate three prospective scenarios that analyze the relationship between subsidy provision and housing deficit reduction in the Metropolitan Area ofSan Luis Potosi, Mexico. The results show that the best-case scenario is one where subsidies are increased by 30% to reduce the housing deficit while avoiding skyrocketing land prices and housing costs.